STATISTICAL ANALYSIS OF BANKING SYSTEM PROBLEMS. (Multidisciplinary Journal of Science and Technology, 2024)
Ensuring the stability of the banking system, as an important factor in ensuring their solvency, is a necessary condition for ensuring the continuity of payments made in the country's economy. Therefore, forming the stability of the banking system is one of the main tasks of banking supervision. The article identifies urgent problems related to ensuring the stability of the banking system of the Republic of Uzbekistan and develops scientific proposals aimed at solving them.